2022
DOI: 10.3390/ijms23105756
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiota in the Immunopathogenesis of Endometrial Cancer

Abstract: The female reproductive tract hosts a specific microbiome, which plays a crucial role in sustaining equilibrium and good health. In the majority of reproductive women, the microbiota (all bacteria, viruses, fungi, and other single-celled organisms within the human body) of the vaginal and cervical microenvironment are dominated by Lactobacillus species, which benefit the host through symbiotic relationships, in comparison to the uterus, fallopian tubes, and ovaries, which may contain a low-biomass microbiome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 122 publications
(163 reference statements)
0
9
0
1
Order By: Relevance
“…However, several studies have shown that the endometrium is colonized by bacterial strains that differ from the vaginal microbiota (Moreno et al, 2016;Chen et al, 2017). Dysbiosis of the endometrial microbiota is likely to lead to endometrial cancer (Walther-António et al, 2016;Sobstyl et al, 2022), polyps (Fang et al, 2016), endometriosis (Akiyama et al, 2019;Wessels et al, 2021), endometritis (Moreno et al, 2018;Hernandes et al, 2020), and recurrent pregnancy loss (Łaniewski et al, 2020). A recent study confirmed that Porphyromonas somerae represents a suitable biomarker for endometrial cancer (Walsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that the endometrium is colonized by bacterial strains that differ from the vaginal microbiota (Moreno et al, 2016;Chen et al, 2017). Dysbiosis of the endometrial microbiota is likely to lead to endometrial cancer (Walther-António et al, 2016;Sobstyl et al, 2022), polyps (Fang et al, 2016), endometriosis (Akiyama et al, 2019;Wessels et al, 2021), endometritis (Moreno et al, 2018;Hernandes et al, 2020), and recurrent pregnancy loss (Łaniewski et al, 2020). A recent study confirmed that Porphyromonas somerae represents a suitable biomarker for endometrial cancer (Walsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A low percentage of Lactobacillus in the female vaginal sample is less likely to have a successful embryo implantation, with an interplay between the uterine microenvironment and the host's immune system (Moreno et al, 2022). This involves increased proinflammatory cytokine production in endometrial cells, including interleukin (IL)-1a, IL-1b, IL-17a, and tumor necrosis factor (TNF)-a, due to the estrogen-dependent nature of endometrial cell cytokine production (Sobstyl et al, 2022). However, other groups reported that Proteobacteria, Firmicutes, and Bacteroidetes were prevalent in endometrial samples, while Lactobacillus spp.…”
Section: Endometrial Microbiomementioning
confidence: 99%
“…Gene-disease enrichment analysis of these transcription factors demonstrated a marked enrichment of multiple pathways related to neoplasms, endometriosis and infertility, all pathologies potentially associated with Lactobacillus-dominated microbiota (Fig. 7G) 36,37 . To determine if this enrichment was speci c, we generated random lists of transcription factors from the same motif database and demonstrated only an overlapping enrichment in unrelated craniofacial anomalies, suggesting our ndings are indeed speci c (Supplemental Fig.…”
Section: Crispatus Culture Supernatants Alter Chromatin Accessibilitymentioning
confidence: 99%